Uncivil academics: A qualitative case study on the impact of collegial breakdown on team teaching and student engagement. - Mbanjwa, Sibonelo Thanda (Student’s Journal of Health Research Africa, 2025)
Abstract Collegiality among academic staff is a cornerstone of effective higher education delivery, particularly in team-teaching environments. However, breakdowns in collegial relationships, manifested through incivility, lack of communication, and mistrust, can negatively affect collaborative teaching strategies and diminish student engagement. This study examines the impact of deteriorating professional relationships among faculty members on team teaching and student experiences in a South African university context. Methods A qualitative case study design was employed at a South African university between February and April 2022. Data were collected through semi-structured interviews and focus group discussions. A purposive sample of 18 participants was selected: 12 academic staff involved in team-taught modules and 6 final-year undergraduate students enrolled in those modules. Thematic analysis, guided by Braun and Clarke’s six-phase approach, was used to identify patterns in experiences related to collegiality, pedagogical collaboration, and classroom engagement. Results Of the 12 academic staff participants, 7 were male and 5 female, with an average of 11 years of teaching experience (range 6–18 years). The student group included 4 females and 2 males, with a mean age of 22 years. Findings revealed that 9 of 12 staff reported recurring tensions, poor communication, and unresolved conflicts that disrupted coordinated teaching efforts. These breakdowns led to inconsistencies in lecture content delivery, unclear role allocations, and a lack of mutual support. Students reported a decline in class coherence, conflicting feedback from instructors, and reduced interest in the learning material. Overall, collegial breakdown was found to contribute to fragmented teaching and lower student engagement levels. Conclusion Collegial breakdowns undermine the integrity and effectiveness of team teaching, leading to disjointed course delivery and student dissatisfaction. Recommendation Institutions should establish conflict resolution platforms, enforce codes of collegial conduct, and provide professional development workshops on teamwork and academic civility to foster sustainable collaboration.